RENAISSANCE FEATURES IN MUSIC "NEW ART" (Spectrum Journal of Innovation, Reforms and Development, 2022)
It can be said that in addition to the art of opera, The Palace and the noble classes of neutakht had at their disposal various manifestations of European chamber-instrumental and concert music from the middle of the XVIII century. At the palace, along with wonderful Italian singers, there were also skillful instrumentalists of all kinds of musical instruments, who mainly preferred to perform samples of their creations. The image of a professional musician, formed at the end of the XIII-XIV centuries, highlights the image of an enlightened aristocrat who creates music for the church and secular society, the emergence of choral performance in European countries, the scientific views of Russian composers who communicated with Western culture. The musical culture of the 70s of the XVIII century is substantiated.